Um mecanismo integrado de cache e prefetching para sistemas de entrada e saída de alto desempenho - Dodonov, Evgueni (Universidade Federal de São Carlos, 2004)
An integrated caching and prefetching mechanism for a parallel network file system has the potential to improve both the speed and performance of I/O operations. Different cache policies and algorithms can be used in the system. Different prefetching mechanisms can also be used in the system. The performance of the I/O operations can also be influenced by other techniques, such as the assynchronous write, cache consistency and cache space organization and distribution. This work presents the implementation of an integrated caching and prefetching architecture, intended to be used in distributed file systems. Also, this work elaborates an adaptive access pattern discovery algorithm to be used in prefetching mechanisms, denominated CPS, and two prefetching strategies, called prefetch-on-empty and limited aggressive. As the case studies, this work presents two multimedia servers a on-demand multimedia server, and a streaming media server. The influence of the proposed cache and prefetching mechanisms on tested applications is discussed. This work presents and discusses the functionality of integrated caching and prefetching mechanisms, benchmarking the implemented algorithms and overviewing the influence of chosen policies on the applications behavior.
Keywords: Sistemas distribuídos; Arquivos paralelos; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO